Becoming Insane: The Death of Arch Wolfe at the Canton Asylum for Insane Indians - Devon Mihesuah (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: ableism; Canton Asylum; settler colonialism; Arch Wolfe; Cherokee Nation; history; Indigeneity; institutionalization; St. Elizabeths Hospital; violence